The Role of Indonesian Language in Building National Civilization and Cultural Identity - Cecep Wahyu Hoerudin; Beni Ahmad Saebani (International Journal of Nusantara Islam, 2026)
This study aims to analyze the role of the Indonesian language in shaping social behavior and constructing national civilization within both national and international contexts. The research focuses on understanding language as a symbolic system that constructs values, norms, and collective meanings in social life. Key concepts include language as cultural capital, social behavior as a product of symbolic interaction, and civilization as an institutionalized value system. The study employs a qualitative approach through content analysis of contemporary literature in sociology, anthropology, and sociolinguistics. The scope of analysis covers the functions of the Indonesian language in social, cultural, educational, and cultural diplomacy domains. The main findings reveal that the Indonesian language serves as an integrative mechanism that strengthens social cohesion, shapes collective ethics, and acts as an instrument of soft power in international relations. The primary challenges identified include the marginal position of Indonesian in global discourse and the erosion of symbolic meaning due to digital culture. The study recommends strengthening language policies based on cultural values and promoting Indonesian as a medium for knowledge production and cultural diplomacy.